EVALUASI PEMBANGUNAN MASS RAPID TRANSIT (MRT) DALAM MENEKAN ANGKA KEMACETAN LALU LINTAS DI RUTE KORIDOR UTARA-SELATAN FASE I STASIUN DUKUH ATAS JAKARTA PUSAT - Amalina Dianathul; Saefudin Zuhri (PRESIDENSI: Jurnal Politik dan Pemerintahan, 2026)
The purpose of this study is to find out and analyze the description of the implementation of the Jakarta Mass Rapid Transit (MRT), the supporting and inhibiting factors, as well as the efforts that have been made to improve MRT services in reducing traffic congestion in Central Jakarta. This study uses a descriptive qualitative research approach. Data collection techniques used are observation, interviews, and documentation. Data analysis in this study uses three components consisting of data reduction, data presentation, and drawing conclusions. The results of the study indicate that the implementation of MRT transportation in the capital has been running very well in terms of facilities and infrastructure and has received a positive response from the community. Where there are factors that hinder implementation during the COVID-19 pandemic and always seek several strategies in order to improve the quality of service.